Study of the biodegradation process of bioplastic films prepared from red marine algae "Galaxaura" in soil - قره علي, أحمد; لايقه, حسام الدين; منى, رئبال (Latakia University Journal -Biological Sciences Series, 2021)
Plastic waste is one of the prominent environmental problems worldwide because it accumulates in the environment causing pollution, hence the importance of this paper is to synthesize biodegradable plastics from marine algae as alternatives to non-degradable plastics. Agar was extracted from the red marine algae "Galaxaura" by direct extraction method with hot water with an average yield of 36.8%, and by hot water extraction method after alkaline treatment with a yield of 16%, and used it in the production of bioplastic films. The bioplastic film sample which buried in soil exhibited biodegrability and a weight loss rate of (42.1%) within 30 days in winter compared to (40.58%) in summer within 120 days.